Review of the Effectiveness of the Loan Interest Subsidy Program for Micro, Small and Medium Enterprises by the Cooperative Office of Small and Medium Enterprises (UKM) Pekanbaru City - Milda, Gustia; Rafi, M. (Department of Public Administration, Muhammadiyah University of Makassar, 2025)
The Pekanbaru City SME Cooperative Office holds a loan interest subsidy program that aims to support the implementation of the National Economic Recovery (PEN) program and assist business actors in running their businesses. In its implementation, business actors must take part by developing their business. But in reality, there are problems for business actors, namely the lack of quality of human resources, difficulties in realizing procedures and permits from the Government, the lack of capital owned by business actors and difficulties in obtaining loans. The research method used in this research was descriptive qualitative. Data collection techniques were carried out using interviews and documentation techniques. The data analysis technique in this research used Nvivo 12 Plus software using the theory of measuring program effectiveness by Sutrisno. The results of this study indicate that from the aspect of understanding the program for business actors, they do not fully understand and are able to deal with the consequences of late payment of loan interest subsidies. The right target indicator has not been able to achieve the objectives of the loan interest subsidy program because there is a Cost Budget Plan (RAB) that does not match the actual conditions. Timely indicators, which are quite slow in the process of distributing the loan interest subsidy program. Then the real change indicator found that the loan interest subsidy program has not been able to bring about changes because there are still many problems that occur such as bad credit, lack of responsiveness, short repayment times, and many who ask for unsecured. From these problems, it can be said that the loan interest subsidy program implemented has not been effective and has not been able to bring impact or change to the community as business actors.